The Determination of Genetic Markers of Age-Related Cancer Pathologies in Populations from Kazakhstan - Djansugurova, Leyla B.; Perfilyeva, Anastassiya V.; Zhunusova, Gulnur S.; Djantaeva, Kira B.; Iksan, Olzhas A.; Khussainova, Elmira M. (Frontiers in Genetics, 2013)
Aging associates with a variety of pathological conditions such as cancer, cardiovascular, neurodegenerative, autoimmune diseases, and metabolic disorders. The oncogenic alterations overlap frequently with the genes linked to aging. Here, we show that several aging related genes may serve as the genetic risk factors for cervical and esophagus cancers. In our study, we analyzed samples obtained from 115 patients with esophageal and 207 patients with cervical cancer. The control groups were selected to match the ethnicity and age of cancer patients. We examined the genes involved in the processes of xenobiotics detoxification (GSTM1 and GSTT1), DNA repair (XRCC1 and XRCC3), and cell cycle regulation and apoptosis (CCND1 and TP53). Our study revealed that deletions of GSTT1 and GSTM1 genes or the distinct point mutations of XRCC1 gene are associated with cervical and esophageal cancers. These results will lead to development of screening for detection of individuals susceptible to esophageal and cervical cancers. Introduction of the screening programs will allow the early and effective preventive measures that will reduce cancer incidence and mortality in Kazakhstan.